2014
DOI: 10.1515/hf-2013-0242
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a very slow disaggregation of lignosulfonates

Abstract: There is still a challenging question about how lignosulfonates (LS), such as non-sulfonated lignins, aggregate and disaggregate in solution. In the literature, the reported critical aggregation concentration (CAC) of LS varies by orders of magnitude. In the present work, the aggregation of a purified sodium LS (NaLS) from a softwood has been studied by size exclusion chromatography and capillary viscometry. It was found that intermolecular aggregates form at relatively high concentrations. Disaggregation is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…These results were found to largely follow the Hofmeister series and are also widely consistent with the reactivity of LS in aqueous salt solutions as found by Myrvold [49] . Further, it was reported that PO 4 3− (HPO 4 2− herein) had the strongest salting‐out effect on LS followed by SO 4 2−[49] which was also found in the present study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results were found to largely follow the Hofmeister series and are also widely consistent with the reactivity of LS in aqueous salt solutions as found by Myrvold [49] . Further, it was reported that PO 4 3− (HPO 4 2− herein) had the strongest salting‐out effect on LS followed by SO 4 2−[49] which was also found in the present study.…”
Section: Resultssupporting
confidence: 92%
“…While in saline solutions, the added ions will lower the charges on the LS molecule leading to less electrostatic repulsion resulting in the formation of denser‐packed oblate ellipsoid spheres. Depending on the pH, the presence of ions and on their concentrations, these spheres are more or less densely packed [48–53] . At low pH, LS is present as a dense, tightly packed spheroid molecule tending to precipitate.…”
Section: Resultsmentioning
confidence: 99%
“…For polyelectrolytes, the origin of the fast mode is attributed to the translational self-diffusion of NaLS molecules, but that of the slow mode is still in debate, but probably Coulomb interactions are one of the main driving forces behind it (Förster et al 1990;Nyström et al 1993;Sedlák 1993;Sedlák 1995). Aggregate formation by means of hydrophobic interaction or hydrogen bonding Yan et al 2010;Myrvold 2013a) is also in discussion.…”
Section: Resultsmentioning
confidence: 99%
“…One report stated that lignosulfonate aggregates are nearly spherical [119], whereas another report illustrated a hollow configuration [121]. As Myrvold demonstrated, aggregation and disaggregation of lignosulfonate is highly dependent on the preparation method and parameters, such as temperature, pH, equilibration time, and concentration [122]. Both a condensed nearly spherical and an open-hollow configuration are therefore realistic.…”
Section: Self-association and Agglomeration In Aqueous Solutionmentioning
confidence: 99%
“…Rana [121]; however, the validity of this measurement is questionable, since UV-spectrometry does not provide a linear response (absorbance increase per concentration increment) at high lignosulfonate concentrations. Overall, lignosulfonate aggregation and de-aggregation is a kinetic process that is especially affected by the origin and composition of the sample [122]. A certain difference in CAC is therefore to be expected between authors, who performed their measurements on dissimilar samples.…”
Section: Self-association and Agglomeration In Aqueous Solutionmentioning
confidence: 99%